Coronary artery calcium scoring in myocardial infarction - Bešlić, Šerif (Radiology and oncology (Ljubljana), 2005)
Background. The aim of this study was to evaluate coronary artery calcium scoring and the assessment of the risk factors in patients with myocardial infarction (MI). Methods. During the period of three years, 27 patients with MI were analyzed. The average age of patients was 66.1 years (46 to 81). Coronary arteries calcium was evaluated by multi row detector computed tomography (MTDC) Somatom Volume Zoom Siemensa, and, retrospectively by ECG gating data acquisition. Semi automated calcium quantification to calculate Agatston calcium score (CS) was performed with 4 x 2.5 mm collimation, using 130 ml of contrast medium, injected with an automatic injector, with the flow rate of 4 ml/sec. The delay time was determined empirically. At the same time several risk factors were evaluated. Results. Out of 27 patients with MI, 3 (11.1 %) patients had low CS (10-100), 5 (18.5%) moderate CS (101499), and 19 (70.4%) patients high CS (>500). Of risk factors, smoking was confirmed in 17 (63.0%), high blood pressure (HTA) in 10 (57.0%), diabetes mellitus in 7 (25.9%), positive family history in 5 (18.5%), pathological lipids in 5 (18.5%), alcohol abuse in 4 (1.8%) patients. Six (22.2%) patients had symptomsof angina pectoris. Conclusions. The research showed high correlation of MI and high CS (>500). Smoking, HTA, diabetes mellitus, positive family history and hypercholesterolemia are significant risk factors. Symptoms are relatively poor in large number of patients.
Keywords: Alcoholism; Alkoholizem; Calcinosis; Coronary Disease; dejavniki tveganja; Diabetes Mellitus; Kajenje; kalcifikacija; Kalcinoza; Koronarna bolezen; Miokardni infarkt; Myocardial Infarction; ožilje; Sladkorna bolezen; Smoking; srčni infarkt; Tomografija radiografska, računalniška; Tomography, X-Ray Computed